Smart Cane: Laser guide as an inclusion tool for the visually impaired - Soares, Johnny Marcos S.; Guerra, Camila Stéfany D.; da Silva, Marcelo Martins; Chaves, Letícia Saraiva; Sampaio, Andréia Libório; Al-Alam, Wagner Guimarães (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
Data from the 2010's Brazilian Institute of Geography and Statistics census show that at least 29 million Brazilians have visual impairment. The assistive technologies development and research advance to promote accessibility and inclusion of people with disabilities. In Human-Computer Interaction, accessibility is related to the flexibility of the users to interact with systems without access impediments. There are several works to assist the visually impaired in their activities, such as screen reader, smart glasses and digital canes. In this paper we present an electronic laser Smart Cane that identifies obstacles on the height of the individual's head. We developed a prototype made of laser sensors with adaptable application, utilizing a calibration process at startup that takes the user's height into consideration, calculating all possible scenarios to help detect obstacles. Lastly, we performed an evaluation by observing users in different usage scenarios and by collecting their opinion through an interview. We obtained satisfactory results on detection and identification of obstacles.